HUBUNGAN PENGGUNAAN ALAT KONTRASEPSI SUNTIK DENGAN SIKLUS MENSTRUASI PADA AKSEPTOR KB SUNTIK DI POLINDES BUNGBARUH KECAMATAN KADUR KABUPATEN PAMEKASAN - Indra Kurniawati; Qurratul A'yun; Maulidya Maulidya (Universitas Islam Madura, 2023)
One of the articles of the Millennium Development Goals (MDGs) agreed upon by 189 countries including Indonesia is the improvement of maternal health and well-being throughout the mother's life cycle, including in terms of contraception and contraceptive effects including menstrual cycle disorders. Injectable contraceptives consist of injectable contraceptives of 3 months and injectable contraceptives of 1 month. Problems that often arise are caused by 3-monthly injectable contraceptives, namely: 60% amenorrhea, 20% oligomenorrhea, and 20% polymenorrhea, while 1 monthly injectable contraceptives 85% of birth control acceptors do not experience problems or menstrual cycle disorders. The purpose of the study was to find out the relationship between the use of injectable birth control contraceptives with menstrual cycle disorders Types of quantitative research with a cross sectional approach. The population was all injectable kb acceptors totaling 180 mothers with a sample of 180 people taken with total sampling techniques. Data collection using questionnaires analyzed using chi square tests. The results of the study found that there were 128 (81.7%) respondents who experienced menstrual cycle disorders and there was a total use of injectable contraceptives for 3 months, namely 156 (86.7%) respondents, while respondents with injectable contraceptives I months were 24 (13.3%) respondents. There is a meaningful relationship between the use of injectable birth control contraceptives with the menstrual cycle in Polindes Bungbaruh, Pamekasan district with p vallue: 0.05. OR value = 0.356 means that those who use 3-month injectable birth control contraceptives are 2.78 times more likely to experience menstrual cycle disorders than respondents who use 1-month injectable birth control contraceptives. Advice that can be given to injectable birth control acceptors who have impaired menstrual cycles to use non-hormonal birth control contraceptives to avoid severe side effects.